PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION DENGAN METODE KNOW WANT TO KNOW LEARNED (KWL) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Ade Imaliyah; Yoni Hermawan; Gugum Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The problem in this research is to determine the effect of the Group Investigation learning model using the Know Want to Know Learned (KWL) method on student learning outcomes in economics subjects. This research was motivated by the low learning outcomes at MA Subulul Huda Darma as indicated by the low average student scores. The research method used was quasi-experimental with a non-equivalent control group design. The population in this study was all 46 class X students, using a saturated sampling technique to determine the sample. The instrument used is a multiple choice test which has been tested for validity, reliability, level of difficulty and distinguishing power. Data analysis was carried out using paired sample t-test, independent sample t-test, and N-Gain calculation. The research results showed that there was a significant increase in learning outcomes in the experimental class which used the Group Investigation learning model with the Know Want to Know Learned (KWL) method compared to the control class which used the conventional learning model. Thus, it can be concluded that the use of the Group Investigation learning model with the Know Want to Know Learned (KWL) method has a positive effect in improving student learning outcomes in economics subjects.